PENGAWASAN PEMERINTAH DAERAH KOTA PEKANBARU DALAM MENERTIBKAN RUMAH BILLIARD PADA TAHUN 2019-2020 - Al Fajri; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Billiard games are now very popular with various circles of society. Not only young people, old people and women now have a lot of love for the game. The number of fans of this billiard game is a golden opportunity for capital owners to increase their rupiah coffers. Until now, in Pekanbaru City, there have been many billiard house businesses. This billiard house business is very vulnerable to various liquors, gambling places and as a place to escape for children when they skip school. Therefore, to minimize the occurrence of violations in the billiard house. Pekanbaru City Government should increase supervision of the billiard house business. The formulation of the problem taken is how to supervise the Pekanbaru City Government in controlling billiard houses in 2019-2020 and what are the inhibiting factors for the Pekanbaru City Government in supervising the billiard house in Pekanbaru City in 2019-2020.The purpose of this study was to find out the supervision of the Pekanbaru City government in controlling billiard houses in 2019-2020 and to find out the inhibiting factors in controlling billiard houses in Pekanbaru City in 2019-2020. The research method used is qualitative research. This type of research is descriptive qualitative. The research location is in Pekanbaru City. Data collection techniques by means of observation, interviews, literature study and study documentation. Data analysis techniques by means of data reduction, data presentation and data verification.The results of the study show that the supervision of the Pekanbaru City Government in controlling billiard houses in 2019-2020 has not run optimally. The monitoring is not optimal yet, it is known that there are still many violations that occur at the billiard house. Some of the factors that cause the supervision to be not optimal are the objectives to be achieved based on the old regulations, the Billiard House Business Owner is not aware of compliance with the law and the sources of supervision are still lacking. Keywords: Local Government Supervision, Expectation, Allocation, Monitoring performance and Correcting action